Predictors of Malaria Incidence in Rural Eastern Indonesia - Mara Ipa1 , Agung Dwi Laksono2 , Endang Puji Astuti1 , Heni Prasetyowati1 , Lukman Hakim1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In Indonesia, the largest number of malaria cases was contributed to by Eastern Indonesia. The study aimedto analyze the predictors of malaria incidence in rural Eastern Indonesia. This study analyzes the 2018Indonesia Basic Health Survey data. In the final stage binary logistic regression was used to determinethe incidence of malaria incidence in 86,382 respondents. Variables analyzed included malaria incidence,regional/province, age, gender, educational level, work type, marital status, wealth status, and healthinsurance. The analysis found that people who lived in rural Maluku and rural North Maluku had a lowerrisk of experiencing malaria than those who lived in rural areas of East Nusa Tenggara. People in ruralWest Papua and rural Papua have a higher risk than those who live in rural East Nusa Tenggara. Men were1.107 times more likely than women to have malaria incidence.People with primary school education were1.237 times more likely to develop malaria than those without education. People with a college educationwere 1.440 times more likely to develop malaria than those without education. People who have a wealth ofpoorer status are 0.804 times more likely to have malaria than those who are poorest. People who have therichest wealth status are 0.851 times more likely to have malaria than those who are the poorest. There were4 variables that have proven to be significant as predictors of incidence in rural Eastern Indonesia, namelyregional/province, gender, education, and wealth.